From roots to DPs, Brazilian Portuguese and English: a model theoretical approach to language variation - Pires de Oliveira, Roberta (Revista Letras, 2021)
The paper develops Pires de Oliveira’s (2020, in press) model theoretical approach to Brazilian Portuguese (BrP) and English. BrP and English are number marking languages, ie when n is first projected, little-n, [n0[X]], where X is a non-categorized root, it is projected as a predicate, <e, t> (Chierchia 2010, 2014, in press). The proposal distinguishes the denotation of n0 from the denotation of a plurality of atoms. The nominal n0 denotes a part-whole non-atomic lattice (Rothstein 2010, 2017). In English, atomicity is mandatory immediately after n0: n1 is projected, generating [n1 [AtP [n0 [X]]]. This predicts no Bare Singulars in argument position in English, mass interpretation via coercion, and also that nominal root [n0 [X]] surfaces in English when AtP is not projected, as in compounds. In BrP, [n0 [X]] surfaces in argument position, because AtP is not mandatory after little-n. This is the bifurcation separating these two types of languages. The absence of grammatical atomicity, leads to under-specification of mass and count. Thus, the Bare Singular is neither mass nor count. Atomicity is induced by the “determiner”, understood in a broad sense: plural inflection, the definite article, some quantifiers. It explores an unitarist approach to the nominal phrase in BrP and proposes a non-canonical derivation. The conclusion explores variation in number marking languages.